"Anything above marijuana takes priority": Obstetric providers' attitudes and counseling strategies regarding perinatal marijuana use. Issue 9 (September 2016) - Holland, Cynthia L.; Nkumsah, Michelle Abena; Morrison, Penelope; Tarr, Jill A.; Rubio, Doris; Rodriguez, Keri L.; Kraemer, Kevin L.; Day, Nancy; Arnold, Robert M.; Chang, Judy C.
Highlights: Obstetric providers are not familiar with risks of marijuana use in pregnancy. Providers perceive marijuana is not as dangerous as other perinatal substance use. Providers admit prioritizing other counseling topics over perinatal marijuana. Providers describe counseling strategies focused on policy and legal consequences. Providers need more information and training on addressing perinatal marijuana. Abstract: Objective: To describe obstetric provider attitudes, beliefs, approaches, concerns, and needs about addressing perinatal marijuana use with their pregnant patients. Methods: We conducted individual semi-structured interviews with obstetric providers and asked them to describe their thoughts and experiences about addressing perinatal marijuana use. Interviews were transcribed verbatim, coded and reviewed to identify themes. Results: Fifty-one providers participated in semi-structured interviews. Providers admitted they were not familiar with identified risks of marijuana use during pregnancy, they perceived marijuana was not as dangerous as other illicit drugs, and they believed patients did not view marijuana as a drug. Most provider counseling strategies focused on marijuana's status as an illegal drug and the risk of child protective services being contacted if patients tested positive at time of delivery. Conclusions: When counseling about perinatal marijuana use, obstetric providers focus more on legal issues than on health risks. They describe needing more information regarding medical consequences of marijuana use during pregnancy. Practice implications: Provider training should include information about potential consequences of perinatal marijuana use and address ways to improve obstetric providers' counseling. Future studies should assess changes in providers' attitudes as more states consider the legalization of marijuana.